Impact of type 2 diabetes on the gene expression of bone-related factors at sites receiving dental implants. Issue 10 (October 2015) - Conte, A.; Ghiraldini, B.; Casarin, R.C.; Casati, M.Z.; Pimentel, S.P.; Cirano, F.R.; Duarte, P.M.; Ribeiro, F.V.
Abstract This study evaluated the influence of type 2 diabetes mellitus (T2DM) on the gene expression of bone-related factors in alveolar bone tissue from sites designated to receive dental implants. Bone biopsies were harvested from sites of planned implants for 19 systemically healthy patients and 35 patients with T2DM (17 with better-controlled T2DM (glycated haemoglobin (HbA1c) levels ≤8%) and 18 with poorly controlled T2DM (HbA1c levels >8%)). The mRNA levels of tumour necrosis factor alpha, transforming growth factor beta, receptor activator of the nuclear factor kappa B ligand (RANKL), osteoprotegerin (OPG), runt-related transcription factor 2, alkaline phosphatase, bone sialoprotein (BSP), type I collagen (COL-I), and osteocalcin were evaluated by quantitative real-time polymerase chain reaction. T2DM up-regulates RANKL levels and the ratio of RANKL/OPG, whereas it down-regulates COL-I and BSP expression (P < 0.05). Higher mRNA levels of RANKL/OPG were observed in the poorly controlled T2DM patients compared to those with better-controlled T2DM and systemically healthy patients (P < 0.05). A lower amount of COL-I and BSP was detected in the biopsies from individuals with poorly controlled T2DM compared to systemically healthy patients (P < 0.05). In conclusion, RANKL, RANKL/OPG, COL-I, and BSP are negatively affected in diabetics. Additionally, the patient's glycaemic status appears to modulate bone-related genes in a different manner.